2016
DOI: 10.1007/s00264-016-3173-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of placing one or two cages in instrumented posterior lumbar interbody fusion

Abstract: Based on the long-term results, instrumented PLIF with a single cage could also be encouraged in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
(36 reference statements)
2
16
0
Order By: Relevance
“…[11][12][13] Surgical approach and placement of interbody cages is another point of consideration, including posterior lumbar interbody fusion, transforaminal lumbar interbody fusion, and posterolateral lumbar interbody fusion, among others. [14][15][16] Scoliosis and brace design, vibration, and posterior instrumentation associated with spinal fusion surgery have all been studied in great detail. [17][18][19][20] In the majority of cases, FEA research of the lumbar spine is performed using CT scan-based models.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Surgical approach and placement of interbody cages is another point of consideration, including posterior lumbar interbody fusion, transforaminal lumbar interbody fusion, and posterolateral lumbar interbody fusion, among others. [14][15][16] Scoliosis and brace design, vibration, and posterior instrumentation associated with spinal fusion surgery have all been studied in great detail. [17][18][19][20] In the majority of cases, FEA research of the lumbar spine is performed using CT scan-based models.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the other three constructs, the von Mises stress on the bone graft was highest in B+P. Previous biomechanical study had demonstrated that the increased stress distribution of intervertebral implants could increase the risk of implant subsidence and dislodgement based on long-term mechanical evaluation ( Zhang M. et al, 2016 ). In present FEA, the increased stress distribution of bone graft may cause postoperative subsidence and displacement of bone graft.…”
Section: Discussionmentioning
confidence: 99%
“…The finite element models were reconstructed with the purpose of evaluating the stress on the implants preoperatively. It has been reported that the increased stress of implant was associated with the postoperative breakage and subsidence risk of implants ( Zhang M. et al, 2016 ; Fan et al, 2019 ). The present study compared the von Mises stress on the rod, pedicle screws, bone graft, and mesh of the different surgical constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al aimed to study how cage placement affects bone remodelling after PLIF surgery. 15 They found that the single cage model demonstrated superior bone development in the bone graft when placed under a constant 400 N axial compressive load. The results showed that in the initial state prior to any bone remodelling, cage stress, cage subsidence and cage dislodgement in the single cage model were all greater than in the coupled cage model.…”
Section: Discussionmentioning
confidence: 99%